Urban Development and Female Convent Fundations in the Audiencia of Santa Fe and the Governement of Popayán (1575-1651) - Brizuela, Sofía; Fernández Villa, Alfonso (Universidad Pedagógica y Tecnológica de Colombia, 2023)
Between 1575 and 1651, 13 convents were founded in a large part of what is now the territory of the Republic of Colombia. In this article, we analyse the links between these convents and the social and economic environment in which they arose. We aim to study how these institutions functioned as true sounding boards and alternatives to the needs of the social whole, which promoted them in a clear interaction of ideological, social, and economic factors.